Oscillatory brain activity in spontaneous and induced sleep stages in flies - Melvyn H. W. Yap (Nature Portfolio, 2017)
Sleep in mammals comprises physiologically and functionally distinct stages. Here, the authors report a transitional sleep stage in Drosophila associated with 7–10 Hz oscillatory activity that can be obtained through activation of the sleep-promoting neurons of the dorsal fan-shaped body.